BioApp: A Mobile Augmented Reality Application to Enhance Junior High School Students’ Academic Performance in the field of Ecological Relationship in Biology. - Baldiviano, Jordan Gregor A; Delgado, Joseph Adriann P; Mora, Joshua O (IC-ITECHS, 2024)
This study investigates student difficulties in understanding biology concepts, particularly during the transition from basic topics like sexuality to complex areas such as genetics. Challenges include reduced engagement and participation, leading to lower performance in assessments. To address these issues, researchers propose "BIOAPP," an Augmented Reality (AR)-based solution designed to enhance learning experiences through interactive and immersive methods. The application prioritizes cost-effective implementation and accessibility, even in low-connectivity areas. The study employs a quantitative research methodology with purposive sampling to assess AR's effectiveness in improving biology education. The resulting mobile game integrates AR to create a dynamic and engaging learning environment, functioning as both an instructional tool and a diagnostic system for tracking student comprehension. This innovative approach aims to renew student interest and participation in biology, offering a transformative and accessible educational solution.